2021
DOI: 10.1111/1756-185x.14177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supervised exercise program and home exercise program in patients with systemic sclerosis: A randomized controlled trial

Abstract: Aim To compare the effects of supervised exercise and home exercise program in patients with systemic sclerosis (SSc). Methods Thirty‐seven SSc patients were included. Patients with SSc were allocated into 2 groups as supervised and home exercise. Breathing, aerobic and resistance exercises were performed with a physiotherapist for 12 weeks in the supervised exercise group. Breathing, posture and aerobic exercises were given to the home exercise group as a home program for 12 weeks. All patients were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We found muscle weakness also has a significant impact upon fatigue perception (Table 2). The beneficial effect of improving physical condition including muscle strength is supported by previous studies [48,49], in which SSc patients, who participated in a complex training program, achieved improvements regarding many aspects of their conditions, including fatigue.…”
Section: Baseline Resultsmentioning
confidence: 64%
“…We found muscle weakness also has a significant impact upon fatigue perception (Table 2). The beneficial effect of improving physical condition including muscle strength is supported by previous studies [48,49], in which SSc patients, who participated in a complex training program, achieved improvements regarding many aspects of their conditions, including fatigue.…”
Section: Baseline Resultsmentioning
confidence: 64%
“…Fatigue in SSc has been found to have a similar prevalence to other rheumatologic diseases and is reported to be one of the most common symptoms experienced. Exercise has been found to reduce fatigue in SSc patients [ 29 31 ]. In the literature, we could not find any study investigating the efficiency of the telerehabilitation program on fatigue in SSc; however, in individuals with multiple sclerosis, fatigue was significantly reduced with a telerehabilitation-based exercise program [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one of the most striking findings of our study was the improvement in SAD post-TOHR. Yakut et al [ 24 ] compared the effects of supervised exercise and a home exercise programme in patients with scleroderma for 12 weeks and observed that pulmonary function assessed by spirometry and by the diffusing capacity for carbon monoxide and the severity of dyspnoea improved significantly only in the group engaging in supervised exercises ( P < 0.05). Notably, improvement in traditional PFTs has not been described in chronic lung diseases after rehabilitation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%